Bryophyte flora of the Huon Peninsula, Papua New Guinea. LXX. Sematophyllaceae (Musci) 1. Acanthorrhynchium, Acroporium, Clastobryophilum, Pseudopiloecium, Radulina and Trichosteleum - Tan, B.C. (2014)
Annales Botanici Fennici